Financial Engineering: An Islamic Perspective - Sami Al Suwailem (Universitas Islam Indonesia, 2007)
Islamic financial industry is growing rapidly. Markets are increasingly appreciat-ing Islamic instruments, and more institutions are willing to provide Islamic services to their clients. However, development of Islamic financial products through appropriate processes of financial engineering has remained an important area of researches. Two issues are always faced by any Islamic financial products in one go, competitiveness and shariah compliance. Not only Islamically acceptable, but any Islamic financial product also must be competitive in order to attract market interest. This paper makes an attempt to systematically address vari-ous fundamental issues for engineering Islamic financial products. The principles and strate-gies for Islamic financial engineering is discussed in this paper. There are four principles for financial engineering, balance, integration, acceptability and consistency. Following these principles, three strategies can be implemented: imitation, mutation and satisfaction.Keywords: Islamic financial product, engineering, financial innovation, legal maximes